Does immediate skin‐to‐skin contact at caesarean sections promote uterine contraction and recovery of the maternal blood haemoglobin levels? A randomized clinical trial - José Miguel Pérez‐Jiménez; Manuel Luque‐Oliveros; Diego Gonzalez‐Perez; Adriana Rivera‐Sequeiros; Cleofás Rodriguez‐Blanco (Nursing Open, 2023)
Abstract Aim We analysed whether immediate skin‐to‐skin contact between the healthy newborn and the mother after a caesarean section has a modulatory role on postpartum haemorrhage and uterine contraction. Design Unblinded, randomized clinical trial, simple random sampling, conducted in women undergoing caesarean sections. Methods Of the population identified, the caesarean section total (N = 359), 23.2% (N = 83) met the inclusion criteria: scheduled caesarean section, accepting skin‐to‐skin contact, good level of consciousness. They were randomly allocated to the intervention group, skin‐to‐skin contact (N = 40), and to the control group, usual procedure (N = 40). There were three losses. Clinical variables: plasma haemoglobin, uterine contraction, breastfeeding, postoperative pain, were measured, and subjective variables: maternal satisfaction, comfort, comparison with previous caesarean section and newborn crying. Results Women with skin‐to‐skin contact had greater uterine contraction after caesarean section. The maternal plasma haemoglobin levels at discharge were significantly higher. It was associated with higher breastfeeding rate, satisfaction, comfort levels and with less maternal pain and less crying in the newborn.